Analysis of the polyphenolic composition of red wines with particular respect to the resveratrol concentration - Kállay, M.; Sárdy Nyitrainé, D. (International Journal of Horticultural Science, 2009)
In our work we have studied red wines of some vine-districts. In the centre of interest was resveratrol. We declared, there was not significant difference between varietys in polyphenol comparison. There was significant variety in anthocyanin and colour-intensity.